New Insights and Potential Therapeutic Interventions in Metabolic Diseases - Clemente-Suárez, Vicente Javier; Martín-Rodríguez, Alexandra; Redondo-Flórez, Laura; López-Mora, Clara; Yáñez-Sepúlveda, Rodrigo; Tornero-Aguilera, José Francisco (International journal of molecular sciences, 2023)
Endocrine homeostasis and metabolic diseases have been the subject of extensive research in recent years. The development of new techniques and insights has led to a deeper understanding of the mechanisms underlying these conditions and opened up new avenues for diagnosis and treatment. In this review, we discussed the rise of metabolic diseases, especially in Western countries, the genetical, psychological, and behavioral basis of metabolic diseases, the role of nutrition and physical activity in the development of metabolic diseases, the role of single-cell transcriptomics, gut microbiota, epigenetics, advanced imaging techniques, and cell-based therapies in metabolic diseases. Finally, practical applications derived from this information are made.